STUDI PENENTUAN NILAI EKIVALENSI MOBIL PENUMPANG (EMP) BERBAGAI JENIS KENDARAAN PADA RUAS JALAN UTAMA DI KOTA PALU - Setiawan, Arief (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
In general, traffic is moving on the highway consists of various types of vehicles. such as motorcycles, passenger cars, trucks, buses and other vehicles. All these vehicles have a dimension, weight and operating characteristics vary. Trucks and buses on the road basically requires space larger than passenger cars. A truck in a traffic flow affects two passenger cars and even more depending on the situation. Buses also requires more space than passenger cars. Passenger car equivalence (PCE) is a conversion factor of various types of vehicles to light vehicles (including passenger cars). Various types of vehicle available at the link can be compared to passenger cars in a way is converted to light vehicles. This study aims to determine the value of passenger car equivalence (PCE) from several types of vehicles that are often found in Palu.Retrieving data with survey for the links Sam Ratu Road and Road W. Monginsidi for 16 hours. The samples will be used for the calculation of PCE used at peak hours with traffic flow in saturated conditions, data retrieval is done by using a video camera (handy cam). The method used to calculate the PCE value of each type of vehicle is the method of multiple regression using the program MS Excel 2003.The results obtained by the PCE heavy trucks, medium trucks, medium buses and motorcycle respectively by using regression analysis method was successively, 2.53, 1.28, 1.77, 0.17.